RELIGION ISSUES IN SAM SMITH SONG’S LYRICS (A PRAGMATIC ANALYSIS ON LA LA LA SONG) - Indiaty Rukmana; Syaifudin Latif Darmawan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This research is a pragmatic study which focused on the context. Pragmatics is study about meaning that listener has different meaning from speaker. The object of this research is; first, understanding the role of pragmatic theory in analyzing the La La La song lyrics, the second is determine the religion issue on La La La song lyrics and the last is identifying the moral value of La La La song lyrics. The data of this research are song lyrics entitled La La La by Sam Smith. The data are analyzed based on their meaning. The main source of data in this research is the song lyric of Sam Smith’s song, with the data collecting technique is Documentation. This paper is qualitative research based on Pragmatic Analysis. The researcher analyze the lyric song entitle La La La by Sam Smith mainly from Context which focus on Religion Issues. The results of this research are (1) The role pragmatic theory is to make it easier for researcher to interpret the lyrics and connect each stanza with the meaning of a particular context. Recently, researcher infers the meaning of the lyrics. (2) The religion issues in the La La La song lyrics are the words that have been underlined from the analysis table in Chapter 4, 1 of “Hiss”, 1 of “Preach”, 1 of “New Messiah”, 2 of “silver lining”, 2 of “your speech”, 4 of “my ears”, and 1 of running of the time. (3) The moral value in the La La La song lyrics are do not cover ears on a good advice. The researcher suggests to anyone who interested in doing research with a similar topic to listen to it and pay more attention to the content of the lyric.